Disseminated cerebral thrombotic microangiopathy in a patient with adult's Still disease - Renan B. Domingues; Ana Maria Casati da Gama; Eliana B. Caser; Carlos Musso; Maria Carmen S. Santos (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: The aim of this report is to describe a fatal disseminated thrombotic micoangiopathy with renal, pancreatic, and cerebral involvement in a patient with recently diagnosed adult's Still disease (ASD). CASE REPORT: A previously healthy 15 year old girl was admitted to our hospital. According to the clinical and laboratory data the diagnosis of adult's still Disease was established. The treatment was begun and few days after an initial improvement a sudden neurologic deterioration with coma and seizures has occurred. Hours later the patient died. Clinical, laboratorial, and pathologic data will be presented. CONCLUSION: To our knowledge this is the second description of a fatal disseminated cerebral thrombotic microangiopathy in a patient with adult's Still disease, but with a much more fulminating evolution than previously reported. Some etiopathogenic mechanisms could be shared in these two disorders explaining this coexistence.